Storytelling with data : a data visualization guide for business professionals - Knaflic, Cole Nussbaumer (Wiley, 2015)
Sometimes it is easy to generate charts and graphs look fine to you, but don't clearly communicate the information that they represent. Knaflic's own knack for clarity will help you sharpen your message when using data in your business presentations.